Roles of doping in enhancing the performance of graphene/graphene-like semiconductors - Yuqi Zhou; Xinbo He; Mengyang Li (AIP Advances)
Graphene is renowned for its excellent chemical, thermal, mechanical, electrical, and optical properties, which arise from its unique bonding structure. However, graphene is intrinsically a zero-bandgap material, limiting its development in the field of flexible nanoelectronics. To expand the range of applications for graphene in electronic devices, it is crucial to develop the strategies for inducing a bandgap. One of the most effective methods is chemical doping. Doping not only alters the electronic properties of graphene by modifying its inherent gapless nature but also engenders new materials with distinctive and potentially synergistic characteristics. Although there are many reviews on the doped graphene, there is a rare one to discuss the role of doping in enhancing the performance of graphene-based semiconductors. This paper reviews various doping types and their impacts on graphene, emphasizing the effects of boron (B) doping, nitrogen (N) doping, oxygen-group doping, other non-metallic atom or atomic pair doping, and metallic doping. We will further discuss how these dopants affect the geometry, electronic structure, and mechanical properties of graphene. It is expected to be meaningful for further understanding the nature of doped graphene and building new graphene-like structures.